Peran Ekonometrika dalam Perencanaan Pembangunan Daerah - Devi Tridayanti; Ismaul Lili Rahma; Adip Nainul Amani; Gustina Masitoh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The issue of fairness in regional development in Indonesia remains a significant challenge, particularly concerning the disparities between urban and rural areas, Java and outside Java, as well as between the western and eastern regions of Indonesia. This imbalance reflects an uneven distribution of investments influenced by the national political-economic structure. The sectoral development approach has been deemed inadequate in addressing these disparities, making the regional-based approach an alternative option to prioritize development in accordance with local potential. Several regional growth theories, such as the export base theory, resource advantage theory, and neoclassical approach, assert that a region's economic growth heavily depends on the availability of natural resources, labor, capital, and technological innovation. The primary indicator for assessing growth and economic well-being in society is Gross Domestic Product (GDP) The increase in GDP accompanied by a decrease in the unemployment rate serves as an indicator of successful development. Therefore, the strengthening of regional development needs to be accompanied by equitable investment strategies and approaches that are appropriate to local characteristics so that the growth achieved can be inclusive and fair.